2008
DOI: 10.1097/mlg.0b013e318165e33e
|View full text |Cite
|
Sign up to set email alerts
|

Role of Planned Postchemoradiotherapy Selective Neck Dissection in the Multimodality Management of Head and Neck Cancer

Abstract: Neck dissection is a safe and effective procedure and a necessary component of the multimodality management of all head and neck cancer patients with N2-3 disease. It should be performed soon after satisfactory demonstration of primary site disease clearance. Universal deployment of radical surgery appears unnecessary and should, when possible, be abandoned in favor of more selective procedures to lessen morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 14 publications
4
29
0
Order By: Relevance
“…The high overall regional control rate of 95 % in the PND group was in line with the literature [26][27][28]. Although not statistically significant, the overall regional control rate in the SND group was with 87 % lower.…”
Section: Discussionsupporting
confidence: 90%
“…The high overall regional control rate of 95 % in the PND group was in line with the literature [26][27][28]. Although not statistically significant, the overall regional control rate in the SND group was with 87 % lower.…”
Section: Discussionsupporting
confidence: 90%
“…This trend of planned ND was widely used as no modalities for the evaluation of nodal response had yet been developed. Some authors using planned ND reported good nodal control rates and revealed frequent residual nodal metastases in surgical specimens [9][10][11]. Therefore they supported the use of planned ND following radiotherapy.…”
Section: Discussionmentioning
confidence: 55%
“…Nouraie et al and Simon both find that persistent disease is the only independent predictor of regional control and disease-specific survival. 1,14 In other words, viable posttreatment cancer in the specimen is associated with poor survival; whether or not neck dissection impacts this decreased survival remains to be seen. From these prior studies and our current study, it may logically follow that poorly compliant patients are at significantly higher risk of persistent neck disease, hence decreasing disease specific survival.…”
Section: Discussionmentioning
confidence: 98%
“…While the majority of articles show that neck dissection is safe and effective, Nouraei, et al noted a 20% major postoperative complication rate including swallowing deterioration, perioperative cardiac dysfunction, wound infection with bleeding, unplanned postoperative tracheotomy, perioperative sepsis, and shoulder morbidity requiring an Eden-Lange procedure. 1 While it is generally safe and often times necessary to perform postchemoradiation neck dissections, this surgery may incur morbidity. Accordingly, it would be ideal to develop a strategy to accurately predict which patients are most likely to harbor residual disease, and perhaps most benefit from neck dissection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation